Does TikTok Effective in Stimulating Language Development for Children Aged 5-6? - Karimah, Lutfiana Silvi; Rollie C. Deporos, Saprolla; Kustiawan, Usep; Twinsari Maningtyas, Damayani (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – This study aims to find the effect of using the TikTok application on the language skills development of children aged 5-6 years, including speaking, reading, delivering expressions, and understanding stories in group B at TK Laboratory UM Blitar City.Design/methods/approach – The research method used is quasi-experimental with One-Group Pre-test Post-test Design. The data was obtained through observation. The number of samples is 14 children in class B-3.Findings – Based on the results of the t-test calculations using the Paired Samples Test, the tcount was 15,716 with a significance level of 5%, more significant than the ttable with a value of 2.16. While the significance value obtained is 0.000 <0.05, then H0 is rejected, and H1 is accepted. Thus, there is a significant average difference between the pre-test and post-test scores.Research implications/limitations – This study interpreted that there is a good influence in the use of the TikTok application on the development of language skills of children aged 5-6 years.Practical implications – The results show that using the TikTok application for children's learning media can be done by viewing the educational content consisted in the application.Originality/value – Researchers highlighted that social media could be an alternative learning tool that improves student development skills. Paper type: Research paper